Performance of hybrid solar-biomass dryer (Nepal Journal of Environmental Science, 2017)
Drying of agriculture product is energy intensive and traditional open sun drying is associate with many problems. Use of solar dryer is one of the alternative options. However, it is problematic in rainy and cloudy days. In order to measure the efficiency of solar/biomass hybrid dryer was proposed. A solar/biomass hybrid dryer was fabricated in RECAST Lab. Wood blocks were used as fuel for the gasifier stove. Biomass burning gasifier stove was integrated with solar dryer as an auxiliary heat source through a heat exchanger. The hybrid system of biomass with solar dryer ensures to provide continuous heat when needed. Due to the intermittent nature of sun, especially in rainy or cloudy season, food materials being processed get spoiled. A hybrid solar/biomass drying system solve such problems. Experiments were conducted to test performance of hybrid solar dryers by drying chili and banana. During the load test, conducted for chili, 16 kg of ripen chili with initial moisture content 72.58% (w. b.) was dried to moisture content of 7.13% (w. b.) in 20 hours. The result indicated that drying of chili was faster, within 20 hours (2 days), in natural sunny weather, against 48 hours (5 days) in open sun drying during April, in Kathmandu. Overall efficiency of drying system was found to be 4.29%.